2010
DOI: 10.1016/j.aap.2010.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of driving after alcohol and drug use among adolescents in Valencia (Spain)

Abstract: a b s t r a c tBackground: Driving under the influence of alcohol and drugs has been identified as a risk factor for road traffic crashes. We have assessed the prevalence and predictor factors for driving after alcohol and drug use by adolescents. Methods: A cross-sectional survey involving 11,239 students aged 14-18 years from 252 private and public schools in the Valencia region of Spain was conducted. The prevalence and predictors of driving after alcohol use, alcohol and drug use, or drug use during the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 23 publications
1
12
0
1
Order By: Relevance
“…This fi nding is consistent with other literature associating perceived social norms to risky driving behavior (Scott-Parker et al, 2014;Simons-Morton et al, 2011) and suggests that harm-reduction strategies should focus on early identifi cation of RWI and consider social normative change perspectives. Third, a wide range of research has been conducted in parental behavioral control, parental monitoring knowledge, and their effects on teenage drug and alcohol use and other problem behaviors (Barnes et al, 2000;Dols et al, 2010;Laird et al, 2003;Li et al, 2014b;Roche et al, 2008). Our multivariate logistic regressions of RWI on variables in previous wave fi ndings show that the teenager's parental monitoring knowledge may be protective of RWI.…”
Section: Discussionmentioning
confidence: 82%
“…This fi nding is consistent with other literature associating perceived social norms to risky driving behavior (Scott-Parker et al, 2014;Simons-Morton et al, 2011) and suggests that harm-reduction strategies should focus on early identifi cation of RWI and consider social normative change perspectives. Third, a wide range of research has been conducted in parental behavioral control, parental monitoring knowledge, and their effects on teenage drug and alcohol use and other problem behaviors (Barnes et al, 2000;Dols et al, 2010;Laird et al, 2003;Li et al, 2014b;Roche et al, 2008). Our multivariate logistic regressions of RWI on variables in previous wave fi ndings show that the teenager's parental monitoring knowledge may be protective of RWI.…”
Section: Discussionmentioning
confidence: 82%
“…Due to egocentrism and misapprehension of adolescents to their behaviors, this period is considered as an important phase for beginning high risk behaviors (2), that increases the possibility of negative, unpleasant and problematic consequences for adolescents (3). Based on previous researches, rates of various high risk behaviors such as smoking and alcohol use (4), substance abuse (5), physical aggression (6), risky driving (7), and unprotected sexual relationships (8), are increasing among adolescents. Moreover, children’s participation in risky behaviors has become one of the most important sources of concern for parents (9).…”
Section: Introductionmentioning
confidence: 99%
“…One such policy is increasing the minimum legal drinking age (MLDA) for drinking alcohol in the country to at least the age 21 years. Research suggests the MLDA can be successful in reducing young drivers' alcohol related accident rates significantly (Hingson et al, 2002;McCartt et al, 2010;Tomas Dols et al, 2010;Wechsler et al, 2003;Zakrajsek & Shope, 2006). This policy has demonstrated a positive effect on drink-driving and its related traffic crashes in two dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…It was also noted that car drivers were more likely to have died with BACs of 50 mg/dl (0.05%) or more (30%), while the least prevalence was among truck drivers (9%) (Drummer et al, 2003). A survey also indicated that among teenagers who drink alcohol in Valencia, Spain, 45% reported driving under the influence of alcohol, the majority of whom were males with poor family relations (Tomas Dols et al, 2010). In…”
Section: Prevalence Of Alcohol-impaired Drivingmentioning
confidence: 99%
See 1 more Smart Citation